(untitled) (International Journal of Current Engineering and Technology, 2015)
The Propeller shaft is one of the most important components in transmitting power from the Gearbox to the rear axle. Heavy duty vehicles like buses have their propeller shaft supported by bracket fixed to the chassis. The Center Bearing Bracket plays an important role in overhanging the first half of the propeller shaft with ball bearing to the chassis. It also reduces the length of the propeller shaft between two hook joints. Center Bearing Bracket fatigue failure has been continuously a concern which may lead to operational failure of the propeller shaft which ultimately results in transmission failure. Some common causes of failure are manufacturing, design, maintenance, raw material and the operating conditions. This paper presents the available literature of failure analysis of a propeller shaft mounting bracket and analyzes the premature failure in Center Bearing Bracket. In the Analysis of the Center Bearing Bracket Creo elements / pro-e software is used for modeling and with the help of Ansys the stress and strain analysis were carried out. Based on the results of the existing Bracket dimensions, the new bracket is designed and found that the stresses are within the allowable range.